Work-Life Balance of Generation Y employees in Nonthaburi Province - Lertsuwunseri, Pavornrat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to 1) study the Work-Life Balance level of organization members towards to Generation Y Employees in Nonthaburi Province, and 2) compare the Work-Life Balance of organization members toward to generation Y employees in Nonthaburi Province. The sample group in this study was 384 Generation Y Employees who work in Nonthaburi. Data analysis using statistics, frequency, percentage, mean, standard deviation. Work-life balance was compared using t-test, One-way ANOVA method, and pairwise comparisons were performed using Scheffé at the statistical significance level .05. The statistical data analysis was performed which were frequency, percentage, mean, and standard deviation. The comparison of the Work-Life Balance of organization members was performed by t-test, One-way ANOVA and comparison by the method of significant difference Scheffé’s at .05 significant level. The results of the research revealed that 1) the respondents had a balance between life and work of Generation Y employees in Nonthaburi Province. Overall and side and 2) a comparative study of Work-Life Balance of Generation Y employees in Nonthaburi Province. Education level average monthly income, occupation, and travel time are different. There is a balance between life and work. Overall, there is no difference. But Generation Y employees with different job titles, working hours and working hours have different work-life balance. Overall, the difference was statistically significant at the .05 level.